Efficacy of ovarian tissue cryopreservation in a major European center - Bastings, Lobke; Liebenthron, J.; Westphal, J. R.; Beerendonk, C. C. M.; van der Ven, H.; Meinecke, B.; Montag, Markus; Braat, D. D. M.; Peek, R. (Journal of assisted reproduction and genetics, 2014)
To evaluate the effect of cryopreservation and thawing of ovarian tissue from oncological patients opting for fertility preservation on ovarian tissue viability.